PROFIL KEMAMPUAN KOGNITIF DALAM BERIN RANCANG BANGUN PADA KELOMPOK BERMAIN DI KB TAMAN KREATIFITAS ANAK SHOLEH DUNIA SUZAN KOTA MALANG - Ayu Wulandari; Ika Ratih Sulistiani; Ika Anggraheni (Jurnal Dewantara, 2019)
Early childhood education is education to foster and guide children aged 0 - 6 years. At this age early childhood experiences a sensitive period. Sensitive period is a sensitive period where early childhood easily receives information from the surrounding environment. At the age of 0 - 6 years old children are also times where children are very happy with playing, education and coaching given to students in KB Taman Kreatifitas Anak Sholeh Dunia Suzan Malang City, there are several lessons provided, one of which is learning cognitive abilities. This cognitive ability makes children learn and solve problems, logical thinking and symbolic thinking. The researcher examined the cognitive abilities of every student in KB Taman Kreatifitas Anak Sholeh Dunia Suzan Malang City by using interview, observation and documentary methods involving 10 students. The results of the study are 2 students get 1 star with a percentage of 20%, 2 students get 2 stars with a percentage of 20%, 3 students get 3 stars with a percentage of 30% and 3 students get 4 stars with a percentage of 30%. With these results the profile of cognitive abilities in developing design in KB Taman Kreatifitas Anak Sholeh Suzan Malang City is in stars 3 and 4.